A single-center open-label study to investigate the efficacy and safety of repeated subcutaneous injections of lanreotide Autogel in patients with acromegaly previously treated with octreotide. - Kelly, P; Maher, K; Chew, S; Monson, J; Grossman, AB; Jenkins, P (2010)
OBJECTIVE: To evaluate the efficacy of lanreotide Autogel, a depot preparation of a long-acting somatostatin analogue, in patients with acromegaly who were previously treated with octreotide. METHODS: In a prospective single-center, open-label, comparative study, 13 patients were switched from octreotide treatment (baseline) to lanreotide Autogel therapy at a fixed dosage of 90 mg/4 wk. After 6 injections, the dosage was titrated to 60, 90, or 120 mg/4 wk, on the basis of growth hormone (GH) levels, for a further 6 injections. Mean GH and insulinlike growth factor-I (IGF-I) levels were determined at baseline, during treatment (to 48 weeks), and up to 8 weeks after the last injection. RESULTS: There was no significant change in the proportion of patients with GH and IGF-I control from baseline to week 48 (GH, 85% to 89%; IGF-I, 46% to 62%). Mean GH levels changed little from baseline, but mean IGF-I levels were significantly lower after 32 weeks (P<.05) and 48 weeks (P<.02). Data collected at 6 and 8 weeks after the last injection suggested that the efficacy of lanreotide Autogel can persist for longer than 4 weeks. CONCLUSION: This small study suggests that lanreotide Autogel is at least as effective as octreotide in the control of acromegaly and may last for longer than the recommended 4 weeks. It appears to be a useful alternative to long-acting octreotide in the treatment of acromegaly.